Translating Sanskrit Mathematics - Kichenassamy, Satyanad (Aestimatio)

(untitled) (Institute for Research in Classical Philosophy and Science, 2020)
A discussion of Jean Michel Delire’s Les mathématiques de l’autel védique. Le Baudhāyana Śulbasūtra et son commentaire Śulbadīpikā.